Regulating Monopolies - A Case Example of Google - Jonas Pfeffer; Jan Huckenbeck (Essays der Wissenschaft XIX (Teil 19) - Akademische Essays aus dem Bereich der interdisziplinären Wissenschaft zur Anwendung in Theorie und Praxis, 2020)
Monopolies can have a great impact on economic efficiency and therefore on the market. Thus, states try to avoid either the existence of monopolies or their impacts on the markets. This case study aims at a real case of Google, that has been sued by the European Union for its unlawful behavior. It is important to understand, how monopolies work and how the antitrust laws of the European Commission prevent negative impacts on markets and economies. This paper first explains the foundations of monopolies and how their impacts can be reduced or completely prevented, followed by a definition of the antitrust laws of the European Commission. This paper concludes with an investigation of the European Commission against Google. For this purpose, the details of the case are explained and possible effects are outlined. The conclusion of this paper is that legal action against Google is a viable option, but it is not possible to conclusively evaluate how other solution alternatives would have affected Google's behavior.
Keywords: 330; Monopolies; Google